Analysis of Additively Manufactured 17-4PH Stainless Steel - Coulson, Simon (My University, 2018)
Selective laser melting of nitrogen gas atomized 17-4PH stainless results in up to 50% lower yield strength and 600% higher elongation compared to traditionally processed, wrought 17-4PH. This drastic difference in mechanical properties is commonly attributed to the presence of high volume fractions of retained austenite within the as-built microstructure. The factors leading to the increased level of retained austenite have not been clarified in the literature. Furthermore, the amount of retained austenite reported within published literature vary widely, even with the use of identical process parameters. Manufacturers of selective laser melting systems state that solution annealing and precipitation hardening will achieve traditional mechanical properties, thereby removing all retained austenite. Once again, it is not clear, how the recommended solution and precipitation treatments lead to the desired changes in microstructure. The research within this thesis establishes that there is up to 0.12wt% higher nitrogen content within additively manufactured 17-4PH, compared to traditionally manufactured 17-4PH, as a result of the powder atomization process. The increased nitrogen is able to stabilize the austenitic phase by reducing the Ms temperature below ambient temperatures. Fertiscope bulk phase analysis demonstrates that the processing atmosphere during selective laser melting cannot alter the fraction of retained austenite in the as-built material. The depression of the Ms temperature in the printed parts is confirmed by dilatometry. Due to the TRIP phenomenon, during sample preparation, it was found that the austenite would transform to 80% martensite at the surface. This transformation will greatly impact the phases detected when x-ray diffraction is used for analysis, leading to a wide variety of reported retained austenite values within literature. A mechanism based on the precipitation of nitrides during solution-treatment has been proposed to explain how heat-treatment of the printed parts can lead to a martensitic microstructure with comparable mechanical properties to those of wrought alloys.
Keywords: additive manufacturing; 17-4PH; laser sintering; 3d printing